Coping with Diversity in Dormitories in a Historically White Institute of Higher Learning in South Africa - Jackson, L.T.B; Van de Vijver, F.J.R.; Biela, R. (South African Journal of Higher Education, 2016)
The dormitories of historically white higher learning institutes are becoming diverse in South Africa We were interested in how white students cope with this increased diversity. We consider diversity and multiculturalism as acculturation issues and were interested in how acculturation conditions impact on psychological acculturation outcomes of white students. We propose a dual process model of diversity, consisting of facilitating acculturation resources that lead to satisfaction with life and restricting acculturation demands that lead to ill-health symptoms. Scales of acculturation conditions and outcomes were administered to a convenience sample of 227 Afrikaans-speaking students. Our hypothesized model was confirmed in a path analysis. Acculturation resources were associated with life satisfaction and acculturation demands with ill-health and a reduction in life satisfaction. White Afrikaans females students coped better with diversity compared to their male counterparts. Very negative diversity conditions can erode the benefits of positive acculturation conditions or resources.